Are foods 'healthy' or 'healthier'? Front-of-pack labelling and the concept of healthiness applied to foods. Issue 6 (28th March 2022) - Julia, Chantal; Fialon, Morgane; Galan, Pilar; Deschasaux-Tanguy, Mélanie; Andreeva, Valentina A.; Kesse-Guyot, Emmanuelle; Touvier, Mathilde; Hercberg, Serge
Abstract: While food-based dietary guidelines have been widely disseminated for decades to improve nutritional knowledge in the population about healthy diets, more recent interventions such as front-of-pack labelling have made the differences between the two approaches apparent. While food-based dietary guidelines provide the overarching framework and benchmarks for a healthy diet, based on the current knowledge of the associations between various dietary components and health outcomes, front-of-pack labelling provides guidance to select a specific food, either within a food group or among similar foods belonging to various brands. Labelling foods as 'healthy' or 'unhealthy' raises multiple questions on the criteria used to define the terms and the implications of assigning an absolute healthiness value to an individual food in the context of complex diets. Gradual systems may provide more relative assessments and avoid dichotomisation. The present article presents the inherent differences and the complementarity of food-based dietary guidelines and food choice guidance in the context of food labelling.